Effects of Polyunsaturated Fatty Acids Supplementation on the Meat Quality of Pigs: A Meta-Analysis - Wang, Liyi; Huang, Yuqin; Wang, Yizhen; Shan, Tizhong (Frontiers in Nutrition, 2021)
Polyunsaturated fatty acids (PUFAs) supplementation has been widely discussed as a strategy for improving meat quality in pig production, but the effects are inconsistent. This meta-analysis was performed to comprehensively evaluate its effects on the meat quality and growth performance of pigs. We searched the PubMed and the Web of Science databases (articles published from January 1, 2000 to October 16, 2020) and compared PUFAs-supplemented diets with control diets. We identified 1,670 studies, of which 14 (with data for 752 pigs) were included in our meta-analysis. The subgroup analysis was classified as PUFA source [conjugated linoleic acid (CLA) or linseed], concentration (high or low concentration), and initial stage (growing or finishing pigs). Our analysis found that PUFA supplementation increased the intramuscular fat (IMF) content (WMD = 0.467%, 95% CI: 0.312–0.621, p < 0.001), decreased the meat color L* (WMD = −0.636, 95% CI: −1.225 to −0.047, p = 0.034), and pH 24 h (WMD = −0.021, 95% CI: −0.032 to −0.009, p < 0.001) but had no influence on drip loss, meat color a* and b*, pH 45 min, and growth performance. CLA supplementation improved IMF content (WMD = 0.542%, 95% CI: 0.343–0.741, p < 0.001) and reduced meat color b* (WMD = −0.194, 95% CI: −0.344 to −0.044, p = 0.011). Linseed supplementation increased IMF content (WMD = 0.307%, 95% CI: 0.047–0.566, p = 0.021), decreased meat color L* (WMD = −1.740, 95% CI: −3.267 to −0.213, p = 0.026), and pH 24 h (WMD = 0.034, 95% CI: −0.049 to −0.018, p < 0.001). We discovered an increase on the IMF content in both high and low concentration PUFA supplementation (WMD = 0.461%, 95% CI: −0.344 to −0.044, p < 0.001; WMD = 0.456%, 95% CI: 0.276–0.635, p < 0.001). Furthermore, we also found the effects of PUFA supplementation on meat color L* and pH 24 h are concentration- and stage-dependent. PUFA supplementation can improve the meat quality of pigs, which mainly emerges in greatly increasing IMF content.